A Digital Assessment Method for Multisource Influence Factors on Corrosion Characteristics in the Karst Areas. (25th August 2022) - Gu, Zhanfei; Liu, Zhikui
Abstract : Taking dolomite and limestone in Guilin and Liuzhou regions in the north of Guangxi Province as research objects, this paper analyzed their mineral composition and chemical composition and proposed a digital assessment method for multi-source factors on corrosion characteristics in the Karst areas. Specifically, the chemical corrosion test, the corrosion test under the chemical-temperature actions, and the corrosion test under the action of vibration load are carried out from the digital view, respectively. Four aspects can be found in digital assessment results. Firstly, the dolomite in northern Guangxi mainly has a fine crystalline texture and a massive structure with low content of acid-insoluble matters, while limestone mainly has a powder crystalline texture and a massive structure with high content of acid-insoluble matters, and the purity of both dolomite and limestone are very high. Secondly, the difference of corrosion between dolomite and limestone mainly depends on the ratio of CaO/MgO in their chemical composition and the content of silica and acid insoluble matters. Thirdly, the corrosion rates of pure dolomite and pure limestone are basically the same under the same external conditions. Finally, temperature and vibration load have a relatively large influence on the corrosion rates of dolomite and limestone, and the corrosion rates of dolomite and limestone increase with the increase of temperature, but the influence of vibration load on the corrosion rate is more significant than temperature. This research can provide theoretical basis and technical support for large-scale engineering construction and prevention of karst geologic disasters in karst stone mountainous areas in northern Guangxi.